The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0102-05362012000300035
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium 'Brazilian Fire 101' - New option of color of flowers for the orchid market

Abstract: Establishment of germplasm banks of ornamental species, together with breeding programs is fundamental for the growth of competitive cultivars of flowers that are the same or better quality than those developed in other countries. Around 100 progenies from a crossing between the cultivars Dendrobium 'Tong Chai Gold' and Dendrobium 'Black Jack' were obtained, from 50 plants which were selected and grown in pots in greenhouse conditions to evaluate the blooming stage and to select the progenies. Selection of vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Effect of CW was tested at 0, 5, 10, 15 and 20 % 12-h PP, 1000 lux, 23 ± 2°C 20 % CW was optimal for longest and most pseudobulbs, most and longest leaves and roots, and highest plant fresh weight Soares et al (2013) D. wangliangii The authors referred to the structures as PLBs, but in fact they were protocorms Plant Cell Rep for Dendrobium, mainly because each mature capsule contains 2-3 million seeds with a high percentage of viable seeds that can germinate under in vitro asymbiotic conditions (Paul et al 2012). Another commercially important application of asymbiotic germination is in breeding programmes aimed at accelerating the speed at which new cultivars are obtained (Cardoso 2012). This review aims to examine the available literature (53 studies; Table 1) related to asymbiotic in vitro Dendrobium seed germination (covering 37 species and multiple hybrids; Table 2) in a bid to identify those trends that could assist researchers better formulate a study or conservation programme for commercial or for rare species and hybrids.…”
Section: Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of CW was tested at 0, 5, 10, 15 and 20 % 12-h PP, 1000 lux, 23 ± 2°C 20 % CW was optimal for longest and most pseudobulbs, most and longest leaves and roots, and highest plant fresh weight Soares et al (2013) D. wangliangii The authors referred to the structures as PLBs, but in fact they were protocorms Plant Cell Rep for Dendrobium, mainly because each mature capsule contains 2-3 million seeds with a high percentage of viable seeds that can germinate under in vitro asymbiotic conditions (Paul et al 2012). Another commercially important application of asymbiotic germination is in breeding programmes aimed at accelerating the speed at which new cultivars are obtained (Cardoso 2012). This review aims to examine the available literature (53 studies; Table 1) related to asymbiotic in vitro Dendrobium seed germination (covering 37 species and multiple hybrids; Table 2) in a bid to identify those trends that could assist researchers better formulate a study or conservation programme for commercial or for rare species and hybrids.…”
Section: Seedsmentioning
confidence: 99%
“…Lone et al (2008) also observed a variation of 4.23-6.89 cm in plant height, 5.2-12.87 roots/plantlet, and 0.23-0.63 g of total fresh weight/plantlet after 109 crosses using D. phalaenopsis. Seed propagation is commonly used for conservation of endangered species, and for breeding purposes (Faria et al 2004b;Lone et al 2008;Cardoso 2012). In these cases, genetic variation is a positive factor expected for conservation or development of new cultivars.…”
Section: Basal Mediamentioning
confidence: 99%
“…To have an idea of the importance of this genus in the expansion of world floriculture, only in the Dutch market, the largest in the world, in 2014, 121 million pots of Phalaenopsis were sold generating approximately US$ 500 million [6]. In addition to Phalaenopsis, other genera of economic importance to floriculture include the genera Cattleya, Dendrobium, and Oncidium and their hybrids [7][8][9] as well as Cymbidium and Vanda used for production of potted or even cut flowers.…”
Section: Introductionmentioning
confidence: 99%
“…However, commercial blooming in this hybrid, with higher number of flowers and longer inflorescences were obtained in the second blooming (plants with approximately 1.5 to 2 years after acclimatization), compared with the first ones. This characteristic of rapid flowering has importance for commercial production of orchids because allow the production of flowers in competitive period compared with other commercial genera as Dendrobium and Phalaenopsis orchids (CARDOSO, 2012;CARDOSO et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Breeding of orchids, including Oncidium hybridization are large explored in horticulture, but few papers described the methods of breeding and the segregation of morphological characteristics, as showed for Cattleya Hybrid Group (Cardoso et al 2016;Cardoso, 2010), for Dendrobium (CARDOSO, 2012;FARIA et al, 2009FARIA et al, , 2011FARIA et al, , 2013 and for Oncidium (FARIA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%